Moral evaluation of aggressive behavior in theory and scientific research - Dankiewicz, Malwina (Studia Psychologica: Theoria et praxis, 2012)
Discussed is moral aspect of aggression from the perspective of the following psychological theories: instinct-impulse, evolutionary, socio-cognitive and learning. The results of recent research on moral evaluation of aggressive behavior and aggressor are cited. Described are the criteria that are followed by people for assessing violent acts and those under which some persons are defined as “bad” and others as “good”. Presented is the issue of contemporary approach to the hostile and instrumental aggression, and of their effectiveness as the modes of action. The harmfulness of aggressive behavior, as well as some of the positive aspects of this phenomenon, are indicated.